Games, Play and Gamification in the Bucharest Metropolitan Library as Seen through Facebook Posts - Cernamoriț, Paula-Grațiela (Acta Universitatis Danubius. Communicatio, 2024)
Games, play and gamification, used in organized public library programs, are ways in which libraries can attract a larger audience, especially those who are not yet interested in reading. In this way, contact with the library would enable them to find out about other resources that these cultural institutions offer, thus encouraging them to become regular patrons of non-game services. This paper aims to find out whether these new ways have been used in activities carried out with the public in the Bucharest Metropolitan Library. Research on games, play and gamification in public libraries is very limited in Romania and it could benefit researchers and librarians alike. A content analysis was done on the posts made on Facebook in 2023 by the Bucharest Metropolitan Library. The findings of the study showed that games, play and gamification were used mostly in thematic activities combined with reading, learning and creative workshops. Collaboration with institutions, associations and other organizations has increased the quality of the services offered. The research is valuable in that it presents activities in which librarians have used games, play and gamification, thus offering ideas for all Romanian librarians who could implement these tools on a larger scale in our public libraries.